2016
DOI: 10.1002/asia.201600810
|View full text |Cite
|
Sign up to set email alerts
|

Air‐tolerant Fabrication and Enhanced Thermoelectric Performance of n‐Type Single‐walled Carbon Nanotubes Encapsulating 1,1′‐Bis(diphenylphosphino)ferrocene

Abstract: The thermally-triggered n-type doping of single-walled carbon nanotubes is demonstrated using 1,1'-bis(diphenylphosphino)ferrocene, a novel n-type dopant. Through a simple thermal vacuum process, the phosphine compounds are moderately encapsulated inside single-walled carbon nanotubes. The encapsulation into SWNTs is carefully characterized using Raman/X-ray spectroscopy and transmission electron microscopy. This easy-to-handle doping with air-stable precursors for n-type SWNTs enables the large-scale fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…In this process, additionally, we also elucidated a dramatic increase in conductivity at around 37 °C from 2440 S cm −1 to 3881 S cm −1 . This conductivity enhancement is analogous to the recent works, and the film conductivity close to 4000 S cm −1 is quite high compared to reported buckypapers, especially as the n‐type one.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…In this process, additionally, we also elucidated a dramatic increase in conductivity at around 37 °C from 2440 S cm −1 to 3881 S cm −1 . This conductivity enhancement is analogous to the recent works, and the film conductivity close to 4000 S cm −1 is quite high compared to reported buckypapers, especially as the n‐type one.…”
Section: Figuresupporting
confidence: 89%
“…Since the decrease in the dopant induced conductivity increase, finally, we concluded that encapsulation plays a major role in the enhanced doping. This concept is indeed corresponding to recent results on encapsulation‐induced conductivity enhancement …”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Considering its extraordinary electrochemical stability [13,28,29], AgTFSI, a typical one-electron oxidizer (hole dopant) [30], was used for a p-type dopant. The addition of AgTFSI gradually changed the spectra, achieving (1) the complete suppression of the S 11 band (0.6–0.9 eV), and (2) the significant evolution of one-dimensional plasmon resonance in the MIR region (< 0.6 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The small chloride anions (Cl − ) should interact efficiently with the positive charges on the PDDA main chains. Considering the “hard and soft acids and bases” rule, large anions such as TFSI might effectively compensate delocalized positive charges in the conjugated SWNT backbone. Considering the fully conjugated, narrow‐gap π‐electron SWNT systems, even these minor ionic interactions are crucial for inducing the progression of oxidative p‐type doping and tuning the doping level under ambient conditions…”
Section: Resultsmentioning
confidence: 99%